Abnormal insulin metabolism and decreased levels of mindfulness in type 2 diabetes mellitus - Xue Zhang; Rui Huang; Jiaxin Li; Mingyue Yang; Daowen Zhang; Cancan Liu; Kuanlu Fan (Diabetology & Metabolic Syndrome)
Abstract Objective Disorders of insulin metabolism are strongly associated with a variety of psychological problems. The aim of this study was to investigate the differences in mindfulness levels among type 2 diabetes mellitus (T2DM) patients categorized based on their insulin resistance and β-cell function. Methods A total of 157 T2DM patients were included in this study and divided into four groups according to their levels of insulin resistance and β-cell function. The Five Facet Mindfulness Questionnaire (FFMQ) was employed to assess the mindfulness levels of the patients. Linear regression models were utilized to investigate the relationships between various T2DM categories and mindfulness levels and dimensions. Furthermore, subgroup analyses of key variables were conducted, and mediation analysis was performed to evaluate the sources of differences. Results Significant differences were observed among the four groups in terms of total mindfulness scores and in the dimensions of “Describing,” “Non-judging of Inner Experience,” and “Acting with Awareness” (P < 0.05). Compared to the control group (low HOMA-IR/high HOMA-β), the high HOMA-IR/low HOMA-β group exhibited markedly lower scores in “Non-judging of Inner Experience” (P = 0.02) and “Acting with Awareness” (P < 0.001). The low HOMA-IR/low HOMA-β group demonstrated weaker performance in “Non-judging of Inner Experience” (P = 0.005) and “Describing” (P = 0.002). Conclusion Significant differences in mindfulness levels were found to exist among T2DM patients with varying degrees of insulin resistance and β-cell function. Early-stage diabetes patients, particularly those with lower β-cell function or higher insulin resistance levels, may require additional psychological intervention support to enhance their mindfulness and overall well-being.